Study on Water Characteristic Curve and Shear Characteristics of Typical Unsaturated Silty Clay in Shaoxing. (9th July 2021) - Wu, Ruiqian; Tang, Youzhi; Li, Shaohe; Wang, Wei; Jiang, Ping; Yang, Guang
Abstract : In order to probe into one simplified method to predict the shear strength of Shaoxing unsaturated silty clay, the test method combining unsaturated soil consolidation instrument and conventional direct shear instrument is used to study the shear strength, and the method is compared and verified with the results of equal suction direct shear test. The research results show that the soil water characteristic curve fitted by the measured data points and VG model has obvious stage characteristics in the range of 0 38 kPa, 38 910 kPa, and 910 10000 kPa. The shear strength of unsaturated soil measured by consolidation meter combined with conventional direct shear test is in good agreement with that measured by equal suction direct shear test in the range of 0 500 kPa. The results show that the shear strength, total cohesion, and effective internal friction angle of soil increase slightly with the increase of matric suction in the range of 0 38 kPa. When the matric suction increases from 38 kPa to 500 kPa, the shear strength and total cohesion force of the soil have similar stage characteristics with the SWCC, which first increases and then tends to be stable, while the effective internal friction angle changes slightly. Finally, taking the air-entry value as the demarcation point, an improved model of unsaturated shear strength is proposed by analyzing the error value. Compared with the measured value, the absolute value of relative error is basically kept in the range of 5% 10%, which is close to the measured value.